Variations in the incidence of common mental disorder symptoms in the general population throughout the COVID-19 pandemic: a longitudinal cohort study. (November 2021) - Saunders, Rob; Buckman, Joshua Eusty Jonathan; Fonagy, Peter; Pilling, Stephen; Bu, Feifei; Fancourt, Daisy
Abstract: Background: The COVID-19 pandemic and nationally mandated restrictions to control the virus were anticipated to increase the incidence of mental health issues. So far, little evidence has been found of increases in the use of mental health services. Heterogeneous mental health has been found in general population cohorts during the first 6 months of the pandemic. This study aimed to explore changes in the likelihood of clinically significant mental health issues during 14 months of the pandemic, and to identify individual risk factors for poor mental health. Methods: A cohort was formed of 33 703 adults in England who provided data between March, 2020, and April, 2021 (11 023 [32·7%] aged 60 years or older; 25 567 [75·9%] women; and 1628 [4·8%] from Black, Asian, and Minority Ethnic groups). Trajectories of meeting criteria for clinically significant depression or anxiety each month were estimated with growth mixture modelling through validated screening measure cutoffs (Patient Health Questionnaire-9 scores ≥10 or Generalised Anxiety Disorder Assessment-7 scores ≥8). Sociodemographic and personality-related (Big Five Inventory) risk factors associated with trajectory class membership were identified in multivariable regression models. The study was approved by the University College London Research Ethics Committee (reference 12467/005). Findings: We identified five trajectories for depression and five for anxiety. Participants (general population weighted) in the largest trajectory class (depression: n=20 818 [62%]; anxiety: n=21 167 [63%]) had a less than 5% probability of reporting clinically significant symptoms of depression or anxiety throughout the study period. However, other trajectories represented participants with clinically significant mental health issues: high likelihood of distress throughout the study period (depression: n=4444 [13%]; anxiety: n=4214 [13%]); distress early in the pandemic that decreased within the first four months (depression: n=3 052 (9%); anxiety: n=3 050 [9%]); distress that emerged around five months after the pandemic began (depression: n=2157 [6%]; anxiety: n=2 111 [6%]); and a moderate likelihood of such problems throughout the pandemic study period (March, 2020, to April, 2021) (depression: n=3230 [10%]; anxiety: n=3 159 [9%]). Being in younger age groups (compared with being older than 60 years), female, a carer, having an existing mental health diagnosis, socialising daily pre-pandemic, and higher neuroticism scores were all independently associated with poorer mental health outcomes. Participants from Black, Asian, and Minority Ethnic groups or those living alone were more likely to follow trajectories that changed little in relation to the course of the pandemic. Interpretation: Almost four in ten people followed trajectories with a greater than 50% chance of reporting clinically significant levels of depression or anxiety symptoms during the study period. Sociodemographic, health, and personality factors were associated with differential mental health trajectories. These findings might support targeted public health interventions for those in the highlighted at-risk groups, given the likelihood of developing mental health issues during the course of the pandemic. Funding: This work was supported by the Nuffield Foundation (grant number WEL/FR-000022583), UK Research and Innovation (grant number ES/S002588/1), and Wellcome Trust (grant number 221400/Z/20/Z and 201292/Z/16/Z).